The merry adventures of Robin Hood - Pyle, Howard, 1853-1911 (Sterling Pub., 2004)
The outlaw Robin Hood and his band of merry men share many adventures as they plunder the king's purse, poach his deer, overcome foes, and endear themselves to the poor through their generosity. Includes review questions.